Clinical and Nutritional Care Pathways of Patients with Malignant Bowel Obstruction: A Retrospective Analysis in a Tertiary UK Center. (21st April 2021) - Patel, Pinal S; Fragkos, Konstantinos C.; Keane, Niamh; Cauldwell, Katrine; O'Hanlon, Francis; Rogers, Jennifer; Obbard, Sarah; Barragry, John; Sebepos-Rogers, Gregory; Neerkin, Jane; Mehta, Shameer; Rahman, Farooq; et al.
Abstract: We describe a retrospective cohort study of patients with malignant bowel obstruction to examine their nutritional care pathways between 1.1.16 and 31.12.16 with readmissions until 31.12.17. Data were analyzed by comparing patients who were referred (R) and not referred (NR) for PN. We identified 72 patients with 117 MBO admissions (mean ± SD age:63.1 ± 13.1yrs, 79% female). 24/72 patients were in R group. Predominant primary malignancies were gynaecological and lower-gastrointestinal cancers (76%). 83% patients had metastases (61% sub-diaphragmatically). All patients were at high-risk of malnutrition and baseline mean weight loss was 7%. Discussion of PN at multidisciplinary team meeting (MDT) (22% vs.5%, P  = 0.02) and dietetic contact (94% vs. 41%, P  < 0.0001) were more likely to occur in the R group. In 13/69 MBO admissions in NR group, reasons for non-referral were unclear. Median baseline and follow-up weight was similar (55–55.8 kg). Overall survival was 4.7 (1.4–15.2)months, with no differences by referral groups. We compared a sub-sample of patients who 'may have' required PN ( n  = 10) vs. those discharged on home PN ( n  = 10) and found greater survival in the HPN group (323vs.91 day, P  < 0.01). Our findings highlight disparity in care pathways suggesting that nutritional care should be integrated into clinical management discussion(s) at MDT to ensure equal access to nutritional services.